2016
DOI: 10.1155/2016/2872708
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Anthelmintic Activity of Edible and Ornamental Pomegranate Ethanolic Extracts againstSchistosoma mansoni

Abstract: Due to the development of praziquantel (PZQ) schistosomes resistant strains, the discovery of new antischistosomal agents is of high priority in research. This work reported the in vitro and in vivo effects of the edible and ornamental pomegranate extracts against Schistosoma mansoni. Leaves and stem bark ethanolic extracts of both dried pomegranates were prepared at 100, 300, and 500 μg/mL for in vitro and 600 and 800 mg/kg for in vivo. Adult worms Schistosoma mansoni in RPMI-1640 medium for in vitro and S. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
4
20
0
1
Order By: Relevance
“…In addition, there was a significant reduction in the average diameter of hepatic granuloma in mice treated with DW-3-15, indicating the anti-inflammatory effect of DW-3-15. Similar results have been reported for other compounds, including 8-hydroxyquinoline derivatives and pomegranate extract [41, 42]. Earlier studies reported that the reduction in granuloma diameter was significantly related to egg burden eliminated in the feces [43].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, there was a significant reduction in the average diameter of hepatic granuloma in mice treated with DW-3-15, indicating the anti-inflammatory effect of DW-3-15. Similar results have been reported for other compounds, including 8-hydroxyquinoline derivatives and pomegranate extract [41, 42]. Earlier studies reported that the reduction in granuloma diameter was significantly related to egg burden eliminated in the feces [43].…”
Section: Discussionsupporting
confidence: 85%
“…Existe un renovado interés en los productos naturales como punto de partida para el descubrimiento de medicamentos para combatir las parasitosis, ya que son escasos los recursos para tratarlas (Yones et al, 2016). Por lo cual es necesario desarrollar nuevos medicamentos contra estas enfermedades que afectan al hombre mundialmente.…”
Section: Discussionunclassified
“…Tegumental changes were previously observed in adult worms treated with crude alcoholic extracts of the stem bark, rind and leaf of pomegranate. 20 , 33 Crude extracts of pomegranate leaf and stem bark caused separation of the worm couples and decreased worm’s motility. 20 Our data suggest that these reported tegumental changes and the separation of worm couples are probably, at least in part, due to the ellagitannins of the pomegranate.…”
Section: Discussionmentioning
confidence: 99%
“…This might be behind the uncoupling of worms which was observed in this study and was also caused by crude pomegranate extracts in another study. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation